Failures of the Listed Wooden Buildings in Istanbul - Kuruscu, Ali Osman; Arun, Gorun (TRANS TECH PUBLICATIONS LTD, 2013)
Istanbul, which has been the capital city of different empires throughout history, houses numerous listed architectural and cultural historical buildings. There are diverse applications of timber structures all through Anatolia. As capital city of Ottoman period, construction of timber had high and low periods in Istanbul. As masonry houses have suffered numerous intense and destructive earthquakes, wooden buildings gained importance to be safe especially among rich people. As several fires wiped out thousands of houses and the districts, masonry buildings were made obligatory by law in the form of building regulations. Later however, due to many damages caused by repeated earthquakes, construction of timber buildings was once again allowed under the law. Between the 15th and the 18th centuries, the Turkish dwellings of timber framed construction with brick filling were developed. After the 18th century, the quality of work was decreased; the wall frames constructed without any filling sheathed with timber planks or lathed plaster became popular [1]. Today, although these timber dwellings are listed, they are in very poor condition due to lack of maintenance and wrong interventions. In order to make risk assessment of these structures, more than 20 houses were inspected in Historical Peninsula of Istanbul. This paper will discuss risks sources, assessment of damage level and evaluation of the present condition of these buildings.
Keywords: wooden dwellings in Istanbul; preservation problems of wooden dwellings; listed buildings; failures of wooden structures; Engineering; Materials Science